The AIMS approach: regulating receptivity in patient-provider vaccine conversations - John Parrish-Sprowl; Angus Thomson; Rodger D. Johnson; Susan Parrish-Sprowl (Frontiers Media S.A., 2023)
The World Health Organization named vaccine hesitancy a leading global health threat of modern time. Addressing this public health issue requires a multi-front strategy, one such strategic effort is training health care professionals to respond to reluctant patients/caregivers or those who refuse vaccines. AIMS (Announce, Inquire, Mirror, and Secure) is designed to help HCPs engaged in more productive conversations with patients/caregivers to secure trust, a key behavior leading to higher vaccination rates.